IMPLEMENTATION OF THE PANCASILA STUDENT PROFILE STRENGTHENING PROJECT TO ENHANCE RELIGIOUSITY AND BHINEKA TUNGGAL IKA AT SMK NEGERI 1 KLATEN - Azzahra, Salma Emilia; Ali, Mohammad (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2025)
The challenge of diversity in the era of globalization is an important issue that cannot be avoided by any country, including Indonesia. To maintain unity and strengthen national identity, the values of Bhinneka Tunggal Ika need to be understood and applied in everyday life. This study aims to examine the implementation of the Pancasila Student Profile Strengthening Project (P5) through the theme of Bhinneka Tunggal Ika at SMK Negeri 1 Klaten, focusing on implementation strategies, student involvement, and the impact on strengthening religious values and tolerance for diversity. The research uses a descriptive qualitative method with data collection techniques through interviews, observations, and documentation. The results of the study indicate that the implementation of the Bhinneka Tunggal Ika theme in P5 is able to increase students' awareness of the importance of diversity, strengthen attitudes of tolerance, and increase active participation in cross-cultural project-based activities. However, challenges remain, such as students' limited initial understanding of the concept of diversity and the heterogeneity of their backgrounds. These findings highlight the importance of strengthening diversity literacy from an early age to reinforce unity within the school environment.